The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.talanta.2020.121829
|View full text |Cite
|
Sign up to set email alerts
|

Ion beam analysis (IBA) and instrumental neutron activation analysis (INAA) for forensic characterisation of authentic Viagra® and of sildenafil-based illegal products

Abstract: Ion beam analysis (IBA) and instrumental neutron activation analysis (INAA) for forensic characterisation of authentic Viagra® and of sildenafil-based illegal products

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…2019 analytical method for the analysis of active ingredients in pharmaceutical products and illegal drugs, based on benchtop NMR spectroscopy [ 998 ]; HPLC method on RP-C18 core-shell particulate and monolithic columns for simultaneous analysis of avanafil, sildenafil, apomorphine, trazodone, yohimbine, tramadol and dapoxetine in pharmaceutical dosage forms, counterfeit products and human plasma [ 999 ]; 2020 low-wavenumber Raman spectral database of pharmaceutical excipients for qualitative and quantitative analysis, counterfeit detection and pharmaceutical process control [ 1000 ]; review of the implications of counterfeit medications and the current technological approaches that are used to detect counterfeited pharmaceuticals [ 1001 ]; 2021 HPLC-UV and UPLC-MS/MS methods for the simultaneous analysis of sildenafil, vardenafil, and tadalafil and their counterfeits dapoxetine, paroxetine, citalopram, tramadol, and yohimbine in 50 commercial products including honey sachets, instant coffee and pharmaceutical products [ 1002 ]; Time-Domain Nuclear Magnetic Resonance (TD-NMR) method to detect adulterated pharmaceutical materials [ 1003 ]; electrochemical sensor for determination of acetaminophen in pharmaceutical formulations [ 1004 ]; electrochemical sensor for determination of pharmaceutical compounds [ 1005 ]; paper spray ionization (PSI) coupled to fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) for determining the chemical profiling of 92 samples of counterfeit medicines and ecstasy tablets [ 1006 ]; qualitative and quantitative analyses of pharmaceutical and dietary supplements seized from the black market between January 2016 and December 2019 using GC-MS and LC-HRMS [ 1007 ]; development and validation of a UHPLC-UV method to quantify sildenafil and tadalafil in the presence of six degradation products in the pharmaceutical analysis of genuine and seized medicines [ 1008 ]; NMR method for verifying drug compliance, drug identity, purity and quality [ 1009 ]; ion beam analysis (IBA) procedure to characterize authentic Viagra (R) tablets and sildenafil-based illegal products [ 1010 ]; ATR-FTIR and DSC for the quick detection of counterfeit medicines through the polymer analysis of blister packaging materials [ 1011 ]; discrimination of counterfeit erectile dysfunction medicines using an Ultra-Compact Raman Scattering Spectrometer for the analysis of tadalafil (Cialis), vardenafil (Levitra), and sildenafil (Viagra) tablets purchased on the internet [ 1012 ]; 2022 analytical strategy which enables the structural identification, comprehensive characterization and quantification of monoclonal antibodies in potentially counterfeit samples [ 1013 ].…”
Section: Instrument Focusmentioning
confidence: 99%
“…2019 analytical method for the analysis of active ingredients in pharmaceutical products and illegal drugs, based on benchtop NMR spectroscopy [ 998 ]; HPLC method on RP-C18 core-shell particulate and monolithic columns for simultaneous analysis of avanafil, sildenafil, apomorphine, trazodone, yohimbine, tramadol and dapoxetine in pharmaceutical dosage forms, counterfeit products and human plasma [ 999 ]; 2020 low-wavenumber Raman spectral database of pharmaceutical excipients for qualitative and quantitative analysis, counterfeit detection and pharmaceutical process control [ 1000 ]; review of the implications of counterfeit medications and the current technological approaches that are used to detect counterfeited pharmaceuticals [ 1001 ]; 2021 HPLC-UV and UPLC-MS/MS methods for the simultaneous analysis of sildenafil, vardenafil, and tadalafil and their counterfeits dapoxetine, paroxetine, citalopram, tramadol, and yohimbine in 50 commercial products including honey sachets, instant coffee and pharmaceutical products [ 1002 ]; Time-Domain Nuclear Magnetic Resonance (TD-NMR) method to detect adulterated pharmaceutical materials [ 1003 ]; electrochemical sensor for determination of acetaminophen in pharmaceutical formulations [ 1004 ]; electrochemical sensor for determination of pharmaceutical compounds [ 1005 ]; paper spray ionization (PSI) coupled to fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) for determining the chemical profiling of 92 samples of counterfeit medicines and ecstasy tablets [ 1006 ]; qualitative and quantitative analyses of pharmaceutical and dietary supplements seized from the black market between January 2016 and December 2019 using GC-MS and LC-HRMS [ 1007 ]; development and validation of a UHPLC-UV method to quantify sildenafil and tadalafil in the presence of six degradation products in the pharmaceutical analysis of genuine and seized medicines [ 1008 ]; NMR method for verifying drug compliance, drug identity, purity and quality [ 1009 ]; ion beam analysis (IBA) procedure to characterize authentic Viagra (R) tablets and sildenafil-based illegal products [ 1010 ]; ATR-FTIR and DSC for the quick detection of counterfeit medicines through the polymer analysis of blister packaging materials [ 1011 ]; discrimination of counterfeit erectile dysfunction medicines using an Ultra-Compact Raman Scattering Spectrometer for the analysis of tadalafil (Cialis), vardenafil (Levitra), and sildenafil (Viagra) tablets purchased on the internet [ 1012 ]; 2022 analytical strategy which enables the structural identification, comprehensive characterization and quantification of monoclonal antibodies in potentially counterfeit samples [ 1013 ].…”
Section: Instrument Focusmentioning
confidence: 99%
“…Dalton Transactions with the Buffalo river sediments (NIST 8704). 17 With this procedure, the concentration in parts per million ( ppm) of each element present in the samples was obtained. 2.1.3 Luminescence measurements.…”
Section: Papermentioning
confidence: 99%
“…DART was also used to provide semiquantitative data from drugs after sampling from a variety of porous and nonporous surfaces, including fabrics (85). While DESI and DART are (at best) minimally destructive to the sample, megaelectron volt secondary ion mass spectrometry (MeV-SIMS) is nondestructive and can provide molecular information on the samples under study with minimal sample handling (86).…”
Section: Drugs and Pharmaceutical Productsmentioning
confidence: 99%
“…Recent studies have shown that elemental surface analysis can also play a role in drug profiling. For example, PIXE has been reported to be effective at discriminating between authentic and illegal substances, for example, counterfeit versus authentic Viagra (86). In particular, PIXE is nondestructive, requires no sample preparation, and can identify suitable markers for different products in analytical windows of only a few minutes.…”
Section: Drugs and Pharmaceutical Productsmentioning
confidence: 99%